HUBUNGAN PENGETAHUAN DAN SIKAP REMAJA PUTRI DENGAN PEMERIKSAAN PAYUDARA SENDIRI (SADARI) DI SMAN 2 KARIMUN - Sartini, Titin; Mariyana, Mariyana (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2019)
Breast Self-Exam (BSE) is an attempt or method of breast examination that is carried out regularly and systematically by every woman as an early detection step. Breast cancer can be found early with BSE examination, clinical examination and mammography examination. Early detection of this awareness can reduce mortality rate by 25-30%. The purpose of this study was to determine the relationship of knowledge and attitudes of young women with their own Breast Self-Exam (BSE). This study used an analytical survey method with a cross sectional approach conducted at SMA Negeri 2 Karimun in February-June 2018 with a population of 346 female students and a sample of 186 respondents, takingÂ  sample using purposive sampling with a questionnaire. Data analysis using Chi square analysis technique. Chi square test results obtained p value 0,000 (0,000 <0,05). In conclusion there is a relationship between knowledge and attitudes of young women with their own Breast Self-Exam (BSE). Suggestions that respondents always add insight and increase knowledge about early detection of breast cancer so that breast cancer can be prevented as early as possible.